WEIGHT-LENGTH RELATIONSHIP OF DEMERSAL FISH OF BAIA SUL, FLORIANÓPOLIS, SANTA CATARINA STATE, BRAZIL - dos Passos, Ana Carolina; Cartagena, Beatriz Fernanda Chinchilla; Hostim Silva, Mauricio; Freitas, Matheus Oliveira; Spach, Henry Louis (Arquivos de Ciências do Mar, 2017)
This work presents the weight-length relationship of 35 species of fish belonging to 27 families. The samples were carried out bimonthly from 2001 to 2003 using seines in Saco dos Limões, Baia Sul, Florianópolis, Santa Catarina state, Brazil. The total weight (TW) and total length (TL) data of the species with n ≥ 30 were log-transformed and plotted graphically to identify and remove outliers. The regression analysis was performed to define parameters a and b, from which the weight-length relationship of each species was verified. Growth type determination were classified according to three types: isometric (19 species), positive allometric (12) and negative allometric (4). The weight-length relationship estimate of two species is presented for the first time in Brazil, bringing new information on the life history of species, as well as important results for the evaluation of regional fishery.